Clinical consideration of thrombocytopenia in children - S. Ratna Laksmiastuti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Pediatric patient with the history of bleeding disorder as thrombocytopenia is considered as a clinical case in dentistry. The patient with platelet count below normal has potential risk of bleeding disorders. The situation would be more dangerous if the dentist could not identify the problem. Purpose: The aim of this review is to describe how a dentist must understand the step and management that should be performed in pediatric patient with history of bleeding disorder due to thrombocytopenia. Reviews: Bleeding disorders might be the result of thrombocytopenia, a condition that alter the ability of blood vessels, platelet and coagulation factors in normal hemostatic system. Thrombocytopenia is defined as a platelet count of less than normal (150.000/mm3–400.000/mm3). Etiology, risk factor and preventive method of thrombocytophenia are still unknown. Conclusion: It is concluded that special attention is needed for pediatric patient with thrombocytopenia. A dentist should understand well about this disorder on how to take the history, to do clinical examination, to establish the diagnosis and to decide treatment plan as well as to consult to related collongues.Latar belakang: Penderita anak-anak dengan riwayat gangguan perdarahan yang ditandai dengan adanya trombositopenia merupakan masalah klinis yang ditemukan dalam bidang kedokteran gigi. Beberapa perawatan di bidang kedokteran gigi beresiko menimbulkan terjadinya perdarahan. Keadaan akan berbahaya bila dokter gigi tidak dapat mengidentifikasi masalah. Tujuan: Artikel ini menunjukkan pentingnya seorang dokter gigi memahami dan mengetahui langkah dan tindakan apa yang harus dilakukan, bila suatu saat menghadapi penderita anak-anak dengan riwayat gangguan perdarahan akibat trombositopenia. Review: Gangguan perdarahan adalah suatu kondisi terjadinya penurunan kemampuan dari pembuluh darah, platelet, dan faktor pembekuan pada fungsi normal hemostasis. Trombositopenia adalah jumlah trombosit/platelet dalam darah berada pada jumlah di bawah normal (150.000/mm3–400.000/mm3), yang dapat mengakibatkan terjadinya gangguan perdarahan. Penyebab, faktor risiko dan cara pencegahan kasus trombositopenia belum diketahui dengan pasti. Kesimpulan: Diperlukan perhatian khusus pada penderita anak yang mengalami gangguan perdarahan. Seorang dokter gigi harus mengetahui dengan baik bagaimana menggali informasi tentang riwayat penyakit, melakukan pemeriksaan klinis yang tepat, menegakkan diagnosis, menentukan rencana perawatan serta melakukan rujukan bila diperlukan.